The Long-Term Effects of Reforming Social Security to Relieve Low-Income Households - Tom Krebs; Martin Scheffel; Manuela Barišić; Valentina Sara Consiglio (Wirtschaftsdienst)
Abstract In this paper, we use a macroeconomic model to evaluate two reform proposals that, first, abolish the exemption from social security contributions for marginal employment (“mini jobs”) and, second, reduce social security contributions for low-income earners. Specifically, the first reform proposal lowers social security contributions for individuals with a gross income of less than 1,300 euro per month. The second reform proposal extends the relief to individuals who earn less than 1,800 euro per month. The main findings show that the second reform proposal leads to substantial relief for low income individuals and incentivises unemployed, marginal employed and parttime employed households to increase their labour supply. While there are already positive shortterm effects on employment, the second reform proposal increases longterm employment by 68,900 full-time equivalent units and the ensuing positive effect on employment and productivity is beneficial for the economy, the society, and for fiscal balances.